RNA editing by ADAR1 leads to context-dependent transcriptome-wide changes in RNA secondary structure - Oz Solomon (Nature Portfolio, 2017)
Adenosine deaminase acting on RNA 1 (ADAR1) edits adenosine to inosine. Here the authors, using parallel analysis of RNA secondary structure sequencing, provide evidence that ADAR1 induces sequence-context-dependent RNA secondary structures changes, often leading to stabilization of the RNA duplex.